Exploring training dental implant placement using computer‐guided implant navigation system for predoctoral students: A pilot study. (13th June 2019) - Golob Deeb, Janina; Bencharit, Sompop; Carrico, Caroline K.; Lukic, Marija; Hawkins, Daniel; Rener‐Sitar, Ksenija; Deeb, George R.
Abstract: Introduction: Recent computer‐guided dynamic navigation systems promise a novel training approach for implant surgery. This study aimed to examine learning progress in placement of dental implants among dental students using dynamic navigation on a simulation model. Materials and Methods: Senior students with no implant placement experience were randomly assigned five implant placement attempts involving either three maxillary or four mandibular implants distributed in the anterior/posterior, and left/right segments. Implant placement was planned using a Navident Dynamic Guidance system. Surgical time was recorded. Horizontal, vertical and angulation discrepancies between the planned and placed implant positions were measured using superimposed CBCT scans. Data were analysed with repeated measures regression with Tukey's adjusted pairwise comparisons ( α  = 0.05). Results: Fourteen students participated, with a mean age of 26.1 years and equal males and females. Mean time for implant placement was associated with attempt number ( P  < 0.001), implant site ( P  = 0.010) and marginally related to gender ( P  = 0.061). Students had a significant reduction in time from their first attempt to their second (10.6 vs 7.6 minutes; adjusted P  < 0.001) then plateaued. Overall 3D angulation ( P  < 0.001) and 2D vertical apex deviation ( P  = 0.014) improved with each attempt, but changes in lateral 2D ( P  = 0.513) and overall 3D apex deviations ( P  = 0.784) were not statistically significant. Implant sites were associated with lateral 2D, 2D vertical and overall 3D apex deviation ( P  < 0.001). Discussion: Males were marginally faster than females, had slightly lower overall 3D angulation, and reported higher proficiency with video games. Novice operators improved significantly in speed and angulation deviation within the first three attempts of placing implants using dynamic navigation. Conclusion: Computer‐aided dynamic implant navigation systems can improve implant surgical training in novice population.